Three-dimensional MOF material and preparation method and application thereof
The three-dimensional MOF material prepared by the solvothermal method solves the problems of poor selectivity for organic pollutant removal and limited adsorption capacity in the prior art, and realizes efficient pollutant treatment and material recycling, reducing costs and improving stability.
Patent Information
- Application Number
- CN202411420036.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The prior art has problems such as poor selectivity, limited adsorption capacity, complex regeneration process and high cost in terms of extreme conditions, reduced stability, low degradation efficiency and possible secondary pollution in terms of removal of organic pollutants.
Three-dimensional MOF materials are prepared by solvothermal method. By adjusting the types of ligands and metal ions, optimizing the material properties, Zn-MOF, Co-MOF or Cu-MOF materials are prepared, and their unique electronic structures are used to promote the formation of catalytic active centers and accelerate the formation of Redox reaction of pollutants and the regeneration and utilization of materials are achieved after simple treatment.
Higher pollutant selectivity and adsorption capacity are achieved, and the material exhibits excellent stability and adsorption performance under different environmental conditions, reducing treatment costs and improving application applicability.
Smart Images

Figure CN119306962A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic synthesis, and in particular relates to a three-dimensional MOF material and a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology and the development of society, environmental pollution problems are becoming increasingly serious, especially the emission of organic pollutants has posed a serious threat to human health and the ecological environment. Traditional methods of treating organic pollutants, such as incineration and chemical oxidation, are not only energy-intensive and costly, but may also produce secondary pollution. In recent years, Metal-Organic Frameworks (MOFs) have become a highly potential adsorbent and catalyst material due to their unique porous structure, high specific surface area, good chemical stability and adjustability. They are widely used in gas adsorption, separation, catalytic reactions and other fields.
[0003] At present, the removal of organic pollutants mainly relies on methods such as physical adsorption and chemical degradation. However, although traditional physical adsorbents such as activated carbon can effectively adsorb pollutants, they are not effective for some small molecular pollutants that are difficult to adsorb; although chemical degradation can completely decompose pollutants, it often requires harsh reaction conditions and may produce toxic byproducts.
[0004] Existing technologies have many deficiencies in the adsorption and degradation of pollutants: on the one hand, traditional adsorption materials often have poor selectivity for specific pollutants and are prone to adsorb multiple substances at the same time, resulting in complex subsequent separation and treatment processes; on the other hand, the adsorption capacity of these materials is limited and cannot effectively cope with high concentrations of pollutants, and the regeneration process after use is complicated and costly, which not only causes a waste of resources, but also increases the cost of treatment. In addition, under certain extreme conditions, such as high temperature, high pressure or strong acid and alkali environment, the stability and adsorption efficiency of the adsorbent will decrease significantly. In terms of degradation technology, traditional methods have low degradation efficiency for certain stubborn pollutants (such as persistent organic pollutants), and often require specific environmental conditions to work, which increases the difficulty and cost of operation. At the same time, toxic byproducts may be produced during the degradation process, causing secondary pollution to the environment, and some degradation technologies have a narrow scope of application and are difficult to effectively treat mixed pollutants. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a three-dimensional MOF material and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A three-dimensional MOF material, a Zn-MOF metal organic framework material, a Co-MOF metal organic framework material or a Cu-MOF metal organic framework material prepared by a solvent thermal method using an organic monomer with a structural formula (I) as a ligand and a zinc salt, a cobalt salt or a copper salt as a metal salt;
[0008] The structural formula of the organic monomer is as follows:
[0009]
[0010] As a preferred embodiment of the present invention, the method for preparing the organic monomer having the structural formula (I) comprises the following steps:
[0011] (1) under an inert gas atmosphere, tetrakis(4-bromophenyl)ethylene, 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole, tetrabutylammonium bromide and tetrakis(triphenylphosphine)palladium are added to an organic solvent A, and an alkaline solution B is added and stirred or ultrasonicated to obtain a mixed solution;
[0012] (2) then heating under reflux in an inert gas atmosphere and cooling to room temperature, after rotary evaporation, extraction, and rotary evaporation, adding alcohol and acid A and ultrasonication, and then stirring until the acidification reaction is completed to obtain a suspension;
[0013] (3) The suspension is poured into water to adjust the pH to 7 to obtain a precipitate, which is then washed and dried to obtain an organic monomer having the structural formula (I).
[0014] As a preferred embodiment of the present invention, the molar ratio of tetrakis(4-bromophenyl)ethylene and 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-1H-pyrazole is 1:(5-8); the mass ratio of tetrabutylammonium bromide and tetrakis(triphenylphosphine)palladium is: (0.2-1.0)g:(0.08-0.25)g; the mass ratio of tetrakis(4-bromophenyl)ethylene and tetrabutylammonium bromide is: (1.8-2.5):(0.8-1).
[0015] As a preferred embodiment of the present invention, the organic solvent A is xylene or toluene; the alkaline solution B is an aqueous solution of potassium carbonate, the volume of the alkaline solution B does not exceed 10% of the total volume of the mixed solution, and the mass concentration of potassium carbonate in the aqueous solution of potassium carbonate is 0.4g / mL-0.8g / mL.
[0016] As a preferred embodiment of the present invention, the alcohol is methanol or ethanol, and the acid A is nitric acid, hydrochloric acid or sulfuric acid; the time of the acidification reaction is 4-8 hours; the extraction liquid used in the extraction is a mixture of solvent and water, the solvent is dichloromethane or dichloroethane, and the volume ratio of the solvent to water is 1: (0.5-1); the heating reflux temperature is 100-135°C, the time is 24-72 hours, and the heating reflux method is an oil bath or a sand bath.
[0017] As a preferred embodiment of the present invention, in the step (3), the volume ratio of the suspension to water is 1:(5-10), more preferably, the volume ratio of the suspension to water is 1:(8-10).
[0018] A method for preparing a three-dimensional MOF material comprises the following steps: dissolving an organic monomer having a structural formula (I) in an organic solvent B to obtain a mixed solution, then adding an organic solvent C and a metal salt to heat and react to obtain Zn-MOF, Co-MOF or Cu-MOF; the metal salt is a zinc salt, a cobalt salt or a copper salt.
[0019] As a preferred embodiment of the present invention, when preparing Zn-MOF, the organic solvent C is a mixed solution of methanol, dimethyl sulfoxide, acid B and acid C in a volume ratio of 1: 0.3-0.5: 0.07-0.1: 0.005-0.05; when preparing Co-MOF, the organic solvent C is a mixed solution of methanol, water, dimethyl sulfoxide, acid B and acid C in a volume ratio of 1: 0.1-0.3: 0.3-0.5: 0.07-0.1: 0.005-0.05; when preparing Cu-MOF, the organic solvent C is The invention is a mixed solution of ethanol, dimethyl sulfoxide, acid B and acid C in a volume ratio of 1:0.1-0.3:0.07-0.1:0.005-0.05; the organic solvent B is dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide; the acid B is glacial acetic acid; the acid C is a 10% by mass sulfuric acid solution; the mass concentration of the organic monomer with the structural formula (I) in the mixed solution is 1-10 mg / mL; the amount of zinc salt, cobalt salt or copper salt is 0.01-0.02 g / mL, and the volume is 0.1-0.2 mL.
[0020] As a preferred embodiment of the present invention, the temperature of the heating reaction is 100-130°C, the time is 12-56h, the heating rate is 10-20°C / hour, and the cooling rate is 5-10°C / hour; more preferably, the temperature of the heating reaction is 105-120°C.
[0021] The present invention also claims to protect the use of the three-dimensional MOF material in removing organic pollutants or activating PMS to remove organic pollutants in water.
[0022] More preferably, the Co-MOF material is used in removing organic pollutants.
[0023] More preferably, the three-dimensional MOF material is used to activate PMS to remove organic pollutants in water.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention optimizes the performance of the material by adjusting the types of ligands and metal ions, making it more suitable for the treatment of specific types of organic pollutants. Moreover, the present invention synthesizes three three-dimensional MOF materials for the first time based on a new type of chemical structural formula of pyrazole organic monomers. The three-dimensional MOF material promotes the formation of catalytic active centers with its unique electronic structure, accelerates the redox reaction of pollutants, and not only has higher pollutant selectivity and greater adsorption capacity, but also can achieve material recycling after simple treatment, reduce consumption and reduce overall processing costs. In addition, the three-dimensional MOF material exhibits excellent stability and adsorption performance under different environmental conditions, which improves its applicability in various application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the mass spectrum of the pyrazole organic monomer prepared in Example 1.
[0026] Figure 2 Crystal structure diagram of the three-dimensional Zn-MOF material prepared in Example 4; a) coordination environment of Zn(II) in Zn-MOF, b) three-dimensional structure of Zn-MOF - a-axis, c) three-dimensional structure of Zn-MOF - b-axis, d) three-dimensional structure of Zn-MOF - c-axis.
[0027] Figure 3 Crystal structure diagram of the three-dimensional Co-MOF material prepared in Example 5; a) coordination environment of Co(II) in Co-MOF, b) three-dimensional structure of Co-MOF - a-axis, c) three-dimensional structure of Co-MOF - b-axis, d) three-dimensional structure of Co-MOF - c-axis.
[0028] Figure 4 Crystal structure diagram of the three-dimensional Cu-MOF material prepared in Example 6; a) coordination environment of Cu(II) in Cu-MOF, b) three-dimensional structure of Cu-MOF - a-axis, c) three-dimensional structure of Cu-MOF - b-axis, d) three-dimensional structure of Cu-MOF - c-axis.
[0029] Figure 5 XRD patterns of the Zn-MOF material prepared in Example 4 and the single crystal simulated Zn-MOF material.
[0030] Figure 6 XRD patterns of the Co-MOF material prepared in Example 4 and the single crystal simulated Co-MOF material.
[0031] Figure 7 XRD patterns of the Cu-MOF material prepared in Example 4 and the single crystal simulated Cu-MOF material.
[0032] Figure 8 SEM images and elemental analysis diagrams of the materials prepared in Example 4: a) SEM images and elemental analysis diagrams of the three-dimensional Zn-MOF material prepared in Example 4; b) SEM images and elemental analysis diagrams of the three-dimensional Co-MOF material prepared in Example 4; c) SEM images and elemental analysis diagrams of the three-dimensional Cu-MOF material prepared in Example 4.
[0033] Fig. 9 This is a diagram showing the effect of activating PMS to degrade organic pollutants in bisphenol A using the pyrazole organic monomer prepared in Example 1 and the Zn-MOF, Co-MOF and Cu-MOF prepared in Example 4.
[0034] Fig.10 This is a diagram showing the effect of activating PMS to degrade organic pollutants such as sulfadiazine using the pyrazole organic monomer prepared in Example 1 and the Zn-MOF, Co-MOF and Cu-MOF prepared in Example 4.
[0035] Fig.11 This is a diagram showing the effect of activating PMS to degrade tetracycline organic pollutants using the pyrazole organic monomer prepared in Example 1, and the Zn-MOF, Co-MOF and Cu-MOF prepared in Example 4.
[0036] Fig.12 This is a diagram showing the effect of activating PMS with the pyrazole organic monomer prepared in Example 1, and the Zn-MOF, Co-MOF and Cu-MOF prepared in Example 4 to degrade the organic pollutant 17α-ethynyl estradiol.
[0037] Fig.13 This is a diagram showing the effect of activating PMS to degrade organic pollutants such as methylene blue using the pyrazole organic monomer prepared in Example 1 and the Zn-MOF, Co-MOF and Cu-MOF prepared in Example 4. DETAILED DESCRIPTION
[0038] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0039] The tetrakis(4-bromophenyl)ethylene, 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole, tetrabutylammonium bromide, tetrakis(triphenylphosphine)palladium, potassium carbonate, dichloromethane, sodium hydroxide, N,N-dimethylformamide, methanol, dimethyl sulfoxide, glacial acetic acid, sulfuric acid, zinc nitrate, cobalt nitrate, ethanol, and cupric chloride used in the present invention are all commercially available products.
[0040] Example 1
[0041] A method for preparing a pyrazole organic monomer comprises the following steps:
[0042] (1) First, 0.15 mmol of tetrakis(4-bromophenyl)ethylene was added to 30 mL of xylene under an inert gas atmosphere and stirred at room temperature for 5 minutes. Then, 1 mmol of 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole, 0.2 g of tetrabutylammonium bromide, 80 mg of tetrakis(triphenylphosphine)palladium and 10 mL of 0.5 g / mL potassium carbonate solution were added to the reaction mixture and stirred.
[0043] (2) Reflux at 110°C for 48 hours under an inert gas atmosphere, then cool to room temperature, perform rotary evaporation under pressure at 150°C, cool to room temperature, add 100 mL of dichloromethane to dilute, pour the diluted solution into a separatory funnel, add 100 mL of water, shake and let stand for 5 minutes to remove unreacted metal catalyst and soluble impurities. After transferring the lower layer of the separatory funnel to a round-bottom flask, perform a second rotary evaporation (speed 45 r / min, temperature 60°C, under pressure). Add 50 mL of ethanol solution to the concentrated solution after the rotary evaporation, then add 10 mL of nitric acid and sonicate for 30 minutes to form a light yellow suspension.
[0044] (3) Pour 20 mL of the light yellow suspension into 200 mL of water, adjust the pH to 7 with 0.1 mol of sodium hydroxide to obtain a precipitate, wash it three times with water, and dry it to obtain a polypyrazole organic monomer.
[0045] Example 2
[0046] A method for preparing a pyrazole organic monomer comprises the following steps:
[0047] (1) First, under an inert gas atmosphere, 1 mmol of tetrakis(4-bromophenyl)ethylene was added to 100 mL of xylene and stirred at room temperature for 5 minutes. Then, 5 mmol of 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole, 0.6 g of tetrabutylammonium bromide, 150 mg of tetrakis(triphenylphosphine)palladium and 20 mL of 0.4 g / mL potassium carbonate solution were added to the reaction mixture and stirred.
[0048] (2) Reflux at 100°C for 72 hours under an inert gas atmosphere, then cool to room temperature, perform rotary evaporation under pressure at 150°C, cool to room temperature, add 120 mL of dichloromethane to dilute, pour the diluted solution into a separatory funnel, add 120 mL of water, shake and let stand for 5 minutes to remove unreacted metal catalyst and soluble impurities. After transferring the lower layer of the separatory funnel to a round-bottom flask, perform a second rotary evaporation (speed 45 r / min, temperature 60°C, under pressure). Add 100 mL of ethanol solution to the concentrated solution after the rotary evaporation, then add 20 mL of nitric acid and sonicate for 30 minutes to form a light yellow suspension.
[0049] (3) Pour 20 mL of the light yellow suspension into 160 mL of water, adjust the pH to 7 with 0.1 mol of sodium hydroxide to obtain a precipitate, wash it three times with water, and dry it to obtain a polypyrazole organic monomer.
[0050] The structure is the same as that of Example 1.
[0051] Example 3
[0052] (1) First, 1.9 mmol of tetrakis(4-bromophenyl)ethylene was added to 160 mL of xylene under an inert gas atmosphere and stirred at room temperature for 5 minutes. Then, 15 mmol of 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole, 1.0 g of tetrabutylammonium bromide, 250 mg of tetrakis(triphenylphosphine)palladium and 40 mL of 0.8 g / mL potassium carbonate solution were added to the reaction mixture and stirred.
[0053] (2) Reflux at 135°C for 24 hours under an inert gas atmosphere, then cool to room temperature, perform rotary evaporation under pressure at 150°C, cool to room temperature, add 100 mL of dichloromethane to dilute, pour the diluted solution into a separatory funnel, add 100 mL of water, shake and let stand for 5 minutes to remove unreacted metal catalyst and soluble impurities. After transferring the lower layer of the separatory funnel to a round-bottom flask, perform a second rotary evaporation (speed 45 r / min, temperature 60°C, under pressure). Add 200 mL of ethanol solution to the concentrated solution after the rotary evaporation, then add 40 mL of nitric acid and sonicate for 30 minutes to form a light yellow suspension.
[0054] (3) Pour 40 mL of the light yellow suspension into 200 mL of water, adjust the pH to 7 with 0.1 mol of sodium hydroxide to obtain a precipitate, wash it three times with water, and dry it to obtain a polypyrazole organic monomer.
[0055] The polypyrazole organic monomers prepared in Examples 1-3 are the same. The mass spectrum of the pyrazole organic monomer prepared in Example 1 is as follows: Figure 1 As shown. Figure 1It can be seen that the pyrazole organic monomer was successfully prepared, and the structural formula is
[0056]
[0057] Example 4
[0058] A method for preparing a three-dimensional Zn-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylformamide, preparing a 1 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.2 mL of the above solution, add 1 mL of methanol, 0.4 mL of dimethyl sulfoxide, 0.1 mL of glacial acetic acid, 0.05 mL of sulfuric acid, and 0.1 mL, 0.02 g / mL of zinc nitrate in sequence, ultrasonicate for 10 minutes, and then react at 130°C for 48 hours, with a heating rate of 20°C / hour, cool to room temperature, and cool at a cooling rate of 5°C / hour to obtain a three-dimensional Zn-MOF material.
[0059] A method for preparing a three-dimensional Co-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylformamide, preparing a 1 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.2 mL of the above solution, add 1 mL of methanol, 0.4 mL of dimethyl sulfoxide, 0.3 mL of water, 0.1 mL of glacial acetic acid, 0.05 mL of sulfuric acid, and 0.1 mL, 0.02 g / mL of cobalt nitrate in sequence, and ultrasonicate for 5 minutes, then react at 130°C for 48 hours, with a heating rate of 20°C / hour, cool to room temperature, and cool at a cooling rate of 5°C / hour to obtain a three-dimensional Co-MOF material.
[0060] A method for preparing a three-dimensional Cu-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylformamide, preparing a 1 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Taking 0.2 mL of the above solution, adding 1 mL of ethanol, 0.3 mL of dimethyl sulfoxide, 0.1 mL of glacial acetic acid, 0.0.05 mL of sulfuric acid, and 0.02 g / mL of cupric chloride in sequence, ultrasonicating for 5 minutes, and then reacting at 105°C for 48 hours, with a heating rate of 20°C / hour, cooling to room temperature, and a cooling rate of 5°C / hour to obtain a three-dimensional Cu-MOF material.
[0061] Example 5
[0062] A method for preparing a three-dimensional Zn-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 2 in dimethyl sulfoxide, preparing a 2 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.2 mL of the above solution, add 1 mL of methanol, 0.3 mL of dimethyl sulfoxide, 0.1 mL of glacial acetic acid, 0.05 mL of sulfuric acid, and 0.1 mL, 0.02 g / mL of zinc nitrate in sequence, and ultrasonicate for 10 minutes, then react at 120°C for 48 hours, with a heating rate of 10°C / hour, cool to room temperature, and cool at a rate of 5°C / hour to obtain a three-dimensional Zn-MOF material.
[0063] A method for preparing a three-dimensional Co-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 2 in dimethyl sulfoxide, preparing a 2 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.2 mL of the above solution, add 1 mL of methanol, 0.3 mL of dimethyl sulfoxide, 0.3 mL of water, 0.1 mL of glacial acetic acid, 0.05 mL of sulfuric acid, and 0.1 mL, 0.02 g / mL of cobalt nitrate in sequence, ultrasonicate for 5 minutes, and then react at 120°C for 48 hours, with a heating rate of 10°C / hour, cool to room temperature, and cool at a rate of 5°C / hour to obtain a three-dimensional Co-MOF material.
[0064] A method for preparing a three-dimensional Cu-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 2 in dimethyl sulfoxide, preparing a 2 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.2 mL of the above solution, add 1 mL of ethanol, 0.2 mL of dimethyl sulfoxide, 0.1 mL of glacial acetic acid, 0.05 mL of sulfuric acid, and 0.1 mL, 0.02 g / mL of copper chloride in sequence, ultrasonicate for 5 minutes, and then react at 110°C for 48 hours, with a heating rate of 10°C / hour, cool to room temperature, and cool at a cooling rate of 5°C / hour to obtain a three-dimensional Cu-MOF material.
[0065] Example 6
[0066] A method for preparing a three-dimensional Zn-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 3 in N,N-dimethylacetamide, preparing a 5 mg / mL solution with a concentration of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.4 mL of the above solution, add 2 mL of methanol, 0.6 mL of dimethyl sulfoxide, 0.2 mL of glacial acetic acid, 0.1 mL of sulfuric acid, and 0.2 mL, 0.02 g / mL of zinc nitrate in sequence, ultrasonicate for 10 minutes, and then react at 130°C for 48 hours, with a heating rate of 10°C / hour, cool to room temperature, and cool at a cooling rate of 5°C / hour to obtain a three-dimensional Zn-MOF material.
[0067] A method for preparing a three-dimensional Co-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 3 in N,N-dimethylacetamide, preparing a 5 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.4 mL of the above solution, add 2 mL of methanol, 0.6 mL of dimethyl sulfoxide, 0.5 mL of water, 0.2 mL of glacial acetic acid, 0.1 mL of sulfuric acid, and 0.2 mL, 0.02 g / mL of cobalt nitrate in sequence, and ultrasonicate for 5 minutes, then react at 120°C for 56 hours, with a heating rate of 10°C / hour, cool to room temperature, and cool at a rate of 5°C / hour to obtain a three-dimensional Co-MOF material.
[0068] A method for preparing a three-dimensional Cu-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 3 in N,N-dimethylacetamide, preparing a 5 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.4 mL of the above solution, add 2 mL of ethanol, 0.4 mL of dimethyl sulfoxide, 0.2 mL of glacial acetic acid, 0.1 mL of sulfuric acid, and 0.2 mL, 0.02 g / mL of copper chloride in sequence, ultrasonicate for 5 minutes, and then react at 110°C for 12 hours, with a heating rate of 10°C / hour, cool to room temperature, and cool at a cooling rate of 5°C / hour to obtain a three-dimensional Cu-MOF material.
[0069] Example 7
[0070] A method for preparing a three-dimensional Zn-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylacetamide, preparing a 10 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Taking 0.4 mL of the above solution, sequentially adding 2 mL of methanol, 0.8 mL of dimethyl sulfoxide, 0.2 mL of glacial acetic acid, 0.1 mL of sulfuric acid, and 0.2 mL of 0.02 g / mL of zinc nitrate, ultrasonicating for 10 minutes, and then reacting at 130°C for 24 hours, with a heating rate of 5°C / hour, cooling to room temperature, and a cooling rate of 10°C / hour to obtain a three-dimensional Zn-MOF material.
[0071] A method for preparing a three-dimensional Co-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylacetamide, preparing a 10 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.4 mL of the above solution, add 2 mL of methanol, 0.8 mL of dimethyl sulfoxide, 0.5 mL of water, 0.2 mL of glacial acetic acid, 0.1 mL of sulfuric acid, and 0.2 mL, 0.02 g / mL of cobalt nitrate in sequence, ultrasonicate for 5 minutes, and then react at 130°C for 24 hours, with a heating rate of 5°C / hour, cool to room temperature, and cool at a cooling rate of 10°C / hour to obtain a three-dimensional Co-MOF material.
[0072] A method for preparing a three-dimensional Cu-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylacetamide, preparing a 10 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Taking 0.4 mL of the above solution, sequentially adding 2 mL of ethanol, 0.4 mL of dimethyl sulfoxide, 0.2 mL of glacial acetic acid, 0.1 mL of sulfuric acid, and 0.2 mL, 0.02 g / mL of copper chloride, ultrasonicating for 5 minutes, and then reacting at 115°C for 24 hours, heating at a rate of 5°C / hour, cooling to room temperature at a cooling rate of 10°C / hour, and obtaining a three-dimensional Cu-MOF material.
[0073] The crystal structures of the Zn-MOF, Co-MOF and Cu-MOF metal organic frameworks synthesized in Example 4 are as follows Figure 2 , 3 and 4. The structures of the materials prepared in Examples 5-7 are the same as those in Example 4. Figure 5 , 6 From the XRD analysis of Figures 1 and 7, it can be seen that the XRD of Zn-MOF is simulated according to the single crystal structure, and the Zn-MOF powder synthesized in Example 4 has obvious peaks at 5.62°, 7.44°, 8.92°, 9.70°, 11.38° and 18.24°; in addition, the XRD of Co-MOF is simulated according to the single crystal structure, and it can be seen that the Co-MOF powder synthesized in Example 4 has obvious peaks at 5.68°, 7.32°, 8.90°, 9.68°, 15.84° and 17.90°; the XRD of Cu-MOF is simulated according to the single crystal structure, and it can be seen that the Cu-MOF powder synthesized in Example 4 has obvious peaks at 5.14°, 7.20°, 9.92° and 11.68°, and the synthesized Zn-MOF, Co-MOF and Cu-MOF powders have high crystallinity. The scanning electron microscope photos of Zn-MOF, Co-MOF and Cu-MOF synthesized in Example 4 are as follows Figure 8 As shown, Zn-MOF has a spherical morphology of sheet-like stacking, while Co-MOF and Cu-MOF have block-like morphologies.
[0074] Comparative Example 1
[0075] A method for preparing a three-dimensional Zn-MOF material comprises the following steps: ultrasonically dissolving 1 mmol Zn(NO3)2 and 0.5 mmol sodium terephthalate in 130 mL DMF, transferring the mixture to a reactor and sealing the reactor, heating the mixture to 120°C at a heating rate of 5° / min and reacting the mixture for 24 hours, rinsing the obtained material with pure DMF for 3 times, and vacuum drying the material at 80°C to obtain a three-dimensional Zn-MOF.
[0076] A method for preparing a three-dimensional Co-MOF material comprises the following steps: ultrasonically dissolving 1.2 mmol Co(NO3)2 and 0.8 mmol 2-methylimidazole in 120 mL of a mixed solution of DMF and EtOH (volume ratio of 1:1), transferring the solution to a sealed reactor, heating the temperature to 110°C at a heating rate of 10° / min, reacting the solution for 24 hours, rinsing the obtained material with pure EtOH three times, and vacuum drying the solution at 80°C to obtain a three-dimensional Co-MOF.
[0077] A method for preparing a three-dimensional Cu-MOF material comprises the following steps: ultrasonically dissolving 0.8 mmol Cu(NO3)2 and 0.5 mmol 2-methylimidazole in a 120 mL EtOH solution, transferring the solution to a reaction kettle and sealing the solution, heating the solution to 80°C at a heating rate of 5° / min for 8 hours, rinsing the obtained material with pure EtOH for 3 times, and vacuum drying the solution at 80°C to obtain a three-dimensional Cu-MOF.
[0078] Comparative Example 2
[0079] A method for preparing a three-dimensional Fe-MOF material comprises the following steps: dissolving the pyrazole organic monomer prepared in Example 1 in N,N-dimethylformamide, preparing a 1 mg / mL solution of the pyrazole organic monomer, and ultrasonicating for 5 minutes. Take 0.2 mL of the above solution, add 1 mL of methanol, 0.4 mL of dimethyl sulfoxide, 0.1 mL of glacial acetic acid, 0.05 mL of sulfuric acid, and 0.1 mL, 0.02 g / mL of ferric nitrate in sequence, and ultrasonicate for 10 minutes, then react at 130°C for 48 hours, with a heating rate of 20°C / hour, cool to room temperature, and cool at a cooling rate of 5°C / hour to obtain a three-dimensional Fe-MOF material.
[0080] Effect Example 1
[0081] The degradation effects of the three MOF materials prepared in Examples 4-7 and Comparative Examples 1-2 on tetracycline, bisphenol A, sulfadiazine, 17α-ethynyl estradiol, and methylene blue in different environments were explored. The specific experiments are as follows:
[0082] Test 1: Take out 8 50 ml containers, add 50 mL of tetracycline (20 mg / L) aqueous solution to each container, then add only 10 mg of the polypyrazole ligand prepared in Example 1 (referred to as Lg), only 10 mg of Lg and 0.5 μM PMS to one container, 10 mg of Zn-MOF to one container, 10 mg of Zn-MOF and 0.5 μM PMS to one container, 10 mg of Co-MOF to one container, 10 mg of Co-MOF and 0.5 μM PMS to one container, 10 mg of Cu-MOF to one container, and 10 mg of Cu-MOF to one container and 0.5 μM PMS to one container. Shake the 8 reactions for 45 minutes, take samples at preset time intervals, and filter with a filter having a pore size of 0.45 μm. Collect the adsorbed filtrate in a centrifuge tube, and determine the content of TC by liquid chromatography. Test method: column temperature 30.0 °C. Elution: flow rate 0.6 mL / min, methanol: water (containing 0.1% formic acid) = 50:50.
[0083] Experiment 2: The only difference between this experiment and Experiment 1 is that the organic pollutant was replaced with bisphenol A at the same concentration.
[0084] Experiment 3: The only difference between this experiment and Experiment 1 is that the organic pollutant was replaced by sulfadiazine at the same concentration.
[0085] Experiment 4: The only difference between this experiment and Experiment 1 is that the organic pollutant is replaced by 17α-ethynyl estradiol at the same concentration.
[0086] Experiment 5: The only difference between this experiment and experiment 1 is that the organic pollutant is replaced by methylene blue at the same concentration.
[0087] The results are as follows Figure 9-13As shown in the figure, Zn-MOF, Co-MOF and Cu-MOF can effectively activate PMS to produce reactive oxygen species, and have excellent degradation effects on tetracycline (TC), bisphenol A (BPA), sulfadiazine (SDZ), 17α-ethynyl estradiol (EE2) and methylene blue (MB). Among them, the degradation effect of Co-MOF activated PMS on various pollutants (TC, BPA, SDZ, EE2, MB) is more than 95%, and the removal rate of Cu-MOF activated PMS on SDZ, TC and EE2 is also more than 90%, and it is not affected by the more complex environment in actual wastewater. The degradation effect of Zn-MOF activated PMS on TC is more than 95%. Zn-MOF, Co-MOF and Cu-MOF have certain degradation capabilities for TC, BPA, SDZ, EE2, and MB, among which Co-MOF has the best degradation effect. The polypyrazole ligand and the ligand-PMS system could not effectively remove organic pollutants, and the degradation of tetracycline, bisphenol A, sulfadiazine, 17α-ethynyl estradiol and methylene blue was less than 10%.
[0088] The degradation effects of Zn-MOF, Co-MOF and Cu-MOF prepared in Examples 5-7 on the active oxygen generated by activated PMS on tetracycline, bisphenol A, sulfadiazine, 17α-ethynyl estradiol and methylene blue are similar to those in Example 4. The degradation rates of Zn-MOF, Co-MOF and Cu-MOF prepared in Comparative Example 1 on the active oxygen generated by activated PMS on tetracycline, bisphenol A, sulfadiazine, 17α-ethynyl estradiol and methylene blue are all less than 50%. The degradation rates of Fe-MOF prepared in Comparative Example 2 on the active oxygen generated by activated PMS on tetracycline, bisphenol A, sulfadiazine, 17α-ethynyl estradiol and methylene blue are all less than 60%.
[0089] Effect Example 2
[0090] The Zn-MOF, Co-MOF or Cu-MOF after degrading the organic pollutants in Example 1 was added to anhydrous ethanol and dried after 1 hour; the dried material was subjected to 5 PMS catalytic activation cycles. The degradation effect of the material prepared in Example 4 is shown in Table 1-3.
[0091] Table 1 Zn-MOF+PMS
[0092] Cycle times SDZ BPA TC MB EE2 1 73.45% 36.98% 16.31% 58.16% 60.05% 2 70.11% 30.26% 13.15% 57.31% 53.72% 3 69.33% 28.31% 13.62% 55.51% 48.31% 4 69.12% 26.12% 12.99% 51.89% 45.69% 5 68.94% 25.19% 12.56% 50.66% 44.44%
[0093] Table 2 Co-MOF+PMS
[0094] Cycle times SDZ BPA TC MB EE2 1 99.46% 99.33% 98.65% 99.72% 99.89% 2 96.31% 94.36% 95.31% 97.21% 99.01% 3 95.61% 93.99% 93.44% 96.55% 98.34% 4 94.39% 93.12% 91.35% 95.71% 97.05% 5 94.65% 92.87% 90.06% 95.23% 96.39%
[0095] Table 3Cu-MOF+PMS
[0096] Cycle times SDZ BPA TC MB EE2 1 90.22% 71.31% 99.86% 89.39% 95.36% 2 85.31% 70.01% 97.32% 87.14% 94.33% 3 80.06% 69.31% 95.45% 84.66% 93.12% 4 78.31% 65.69% 92.31% 80.67% 91.99% 5 75.21% 64.31% 91.11% 78.39% 91.02%
[0097] According to Tables 1-3, the Zn-MOF, Co-MOF or Cu-MOF prepared in Example 4 activated PMS to catalyze a variety of organic pollutants and still had a good removal rate, so the Zn-MOF, Co-MOF or Cu-MOF had good recyclability.
[0098] The Zn-MOF, Co-MOF or Cu-MOF prepared in Examples 5-7 and Comparative Examples 1-2 have good cycle stability. However, the degradation rate of organic pollutants catalyzed by the activated PMS of Zn-MOF, Co-MOF or Cu-MOF prepared in Comparative Examples 1-2 is low, less than 50%.
[0099] Effect Example 3
[0100] The Co-MOF prepared in Example 4 or the materials prepared in Comparative Examples 1-2 activated PMS to catalyze the degradation of organic pollutants in tap water and actual water bodies. 10 mg of Co-MOF material was added to tap water or an aqueous solution of Dianchi Lake in Kunming, Yunnan, containing TC (20 mg / L), MB (20 mg / L), EE2 (3 mg / L), SDZ (20 mg / L) and BPA (20 mg / L), respectively. After adding 0.5 μM PMS, the reaction was shaken for 45 minutes, and samples were taken at preset time intervals, and filtered using a filter with a pore size of 0.45 μm. The adsorbed filtrate was collected in a centrifuge tube, and the content of the corresponding pollutants was determined by liquid chromatography and ultraviolet spectroscopy. The degradation rate of organic pollutants is shown in Table 4-5.
[0101] Table 4 Tap water
[0102]
[0103] Table 5 Lake water
[0104]
[0105] According to Table 4-5, it can be seen that under the catalysis of PMS, under the water quality conditions of tap water or lake water, Co-MOF can still maintain a removal rate of more than 93.65% for various pollutants, indicating that Co-MOF has application prospects.
[0106] The Zn-MOF, Co-MOF, Cu-MOF, or Fe-MOF prepared in Comparative Examples 1-2 have weak anti-interference properties, and the degradation rates of organic matter catalyzed by activated PMS are all lower than 40%.
[0107] Effect Example 4
[0108] The simultaneous adsorption-degradation effect of Co-MOF on multiple pollutants in a mixed solution was investigated. 10 mg of Co-MOF or Co-MOF+PMS (0.5 μM) was added to a mixed solution containing TC, BPA, SDZ, EE2 and MB (the concentration of each pollutant was 3 mg / L). The reaction was shaken for 45 minutes, and samples were taken at preset time intervals and filtered using a filter with a pore size of 0.45 μm. The adsorbed filtrate was collected in a centrifuge tube, and the content of the corresponding pollutants was determined by liquid chromatography and ultraviolet spectroscopy. The degradation rate of organic pollutants is shown in Table 6.
[0109] Table 6
[0110]
[0111] As can be seen from Table 6, Co-MOF+PMS can remove a variety of organic pollutants at the same time, and the degradation rate is maintained above 92.30%, which has the potential to treat mixed pollutants in natural water bodies and wastewater.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A three-dimensional MOF material, characterized in that: A Zn-MOF metal organic framework material, a Co-MOF metal organic framework material or a Cu-MOF metal organic framework material prepared by a solvothermal method using an organic monomer having a structural formula (I) as a ligand and a zinc salt, a cobalt salt or a copper salt as a metal salt; The structural formula of the organic monomer is shown in formula (I):
2. The three-dimensional MOF material according to claim 1, characterized in that: The method for preparing the organic monomer having the structural formula (I) comprises the following steps: (1) under an inert gas atmosphere, tetrakis(4-bromophenyl)ethylene, 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole, tetrabutylammonium bromide and tetrakis(triphenylphosphine)palladium are added to an organic solvent A, and an alkaline solution B is added and stirred or ultrasonicated to obtain a mixed solution; (2) then heating under reflux in an inert gas atmosphere and cooling to room temperature, after rotary evaporation, extraction, and rotary evaporation, adding alcohol and acid A and ultrasonication, and then stirring until the acidification reaction is completed to obtain a suspension; (3) The suspension is poured into water to adjust the pH to 7 to obtain a precipitate, which is then washed and dried to obtain an organic monomer having the structural formula (I).
3. The three-dimensional MOF material according to claim 2, characterized in that: The molar ratio of tetrakis(4-bromophenyl)ethylene and 1-(tetrahydro-2H-pyran-2-yl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-pyrazole is 1:(5-8); the mass ratio of tetrabutylammonium bromide and tetrakis(triphenylphosphine)palladium is: (0.2-1.0):(0.08-0.25); the mass ratio of tetrakis(4-bromophenyl)ethylene and tetrabutylammonium bromide is: (1.8-2.5):(0.8-1).
4. The three-dimensional MOF material according to claim 2, characterized in that: The organic solvent A is xylene or toluene; the alkaline solution B is a potassium carbonate aqueous solution, the volume of the alkaline solution B does not exceed 10% of the total volume of the mixed solution, and the mass concentration of potassium carbonate in the potassium carbonate aqueous solution is 0.4g / mL-0.8g / mL; the alcohol is methanol or ethanol, and the acid A is nitric acid, hydrochloric acid or sulfuric acid; the time of the acidification reaction is 4-8h; the extraction liquid used in the extraction is a mixture of solvent and water, the solvent is dichloromethane or dichloroethane, and the volume ratio of solvent to water is 1:(0.5-1).
5. The three-dimensional MOF material according to claim 2, characterized in that: In the step (2), the heating reflux temperature is 100-135° C., the time is 24-72 hours, and the heating reflux method is an oil bath or a sand bath; in the step (3), the volume ratio of the suspension to water is 1:(5-10).
6. A method for preparing a three-dimensional MOF material, characterized in that: The method comprises the following steps: dissolving an organic monomer having a structural formula (I) in an organic solvent B to obtain a mixed solution, then adding an organic solvent C and a metal salt and heating to obtain Zn-MOF, Co-MOF or Cu-MOF; the metal salt is a zinc salt, a cobalt salt or a copper salt.
7. The method for preparing the three-dimensional MOF material according to claim 6, characterized in that: When preparing Zn-MOF, the organic solvent C is a mixed solution of methanol, dimethyl sulfoxide, acid B and acid C in a volume ratio of 1: 0.3-0.5: 0.07-0.1: 0.005-0.05; when preparing Co-MOF, the organic solvent C is a mixed solution of methanol, water, dimethyl sulfoxide, acid B and acid C in a volume ratio of 1: 0.1-0.3: 0.3-0.5: 0.07-0.1: 0.005-0.05; when preparing Cu-MOF, the organic solvent C is a mixed solution of methanol, water, dimethyl sulfoxide, acid B and acid C in a volume ratio of 1: A mixed solution of ethanol, dimethyl sulfoxide, acid B and acid C in a ratio of 0.1-0.3:0.07-0.1:0.005-0.05; the organic solvent B is dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide; the acid B is glacial acetic acid; the acid C is a 10% by weight sulfuric acid solution; the mass concentration of the organic monomer with the structural formula (I) in the mixed solution is 1-10 mg / mL; the amount of zinc salt, cobalt salt or copper salt is 0.01-0.02 g / mL, and the volume is 0.1-0.2 mL.
8. The method for preparing the three-dimensional MOF material according to claim 6, characterized in that: The heating temperature is 100-130°C, the heating time is 12-56h, the heating rate is 10-20°C / hour, and the cooling rate is 5-10°C / hour.
9. The use of the three-dimensional MOF material according to any one of claims 1 to 5 in removing organic pollutants, characterized in that: The three-dimensional MOF material is Co-MOF.
10. Use of the three-dimensional MOF material according to any one of claims 1 to 5 in activating PMS to remove organic pollutants in water.
Citation Information
Patent Citations
Tetraphenylethylene-based polypyrazole nitrogen-containing heterocyclic compound as well as preparation method and application thereof
CN113248437A
Luminescent metal organic framework material as well as preparation method and application thereof
CN116217948A
Cited By
Porous coordination polymer with interpenetrating framework, preparation method and application of porous coordination polymer in separation of ethane / ethylene at high temperature
CN120005212A